Preparation and Characterization of Alkaline Catalyst Waste from Eggshell for Transesterification Reaction - Liong, Phumphairin (Universiti Teknologi PETRONAS, 2016)
The catalytic activities of calcium oxide obtained from eggshell are characterized and evaluated in the transesterification of waste cooking oil. These catalysts are mainly composed of calcium carbonate, which is partially converted into CaO after calcination (900 C for 2 h). CaO catalysts have advantages such as abundant occurrence, low cost, porous structure, and nontoxic. In the research work, the CaO is impregnated with montmorillonite clay and compared with CaO eggshell and commercialized CaO. The catalysts are characterized by EDS, FTIR, TGA, SEM, and BET methods. WCO is treated with acid catalyst to reduce the FFA content before being tested in transesterification process. The catalysts are then undergo transesterification reaction to produce FAME and the yield of biodiesel are tested based on the reaction temperature and reaction time factors.